Fuzzy Analysis of Resonance Frequencies for Structural Inspection of an Engine Cylinder Block. Issue 3 (3rd July 2021) - Mohammadzaheri, Morteza; Amouzadeh, Amirhosein; Doustmohammadi, Mojtaba; Emadi, Mohammadreza; Jamshidi, Ehsan; Ghodsi, Mojtaba; Soltani, Payam
Abstract : Summary : A new inspection technique for complex mechanical structures is proposed in this paper, where a fuzzy inference system carries out structural inspection. The inputs to the fuzzy inference system are the elements of a fault signature, an array of numbers prepared with use of below 5 kHz resonance frequencies of faultless and a number of faulty specimens. Advantage : Below 5 kHz resonance frequencies are easier and less expensive to obtain compared to higher frequency ones. Limit : Due to high expenses of experiments, reliable finite element models were alternatively used to obtain resonance frequencies of the faulty specimens. Results : The developed fuzzy inference system in this research accurately located an under-surface fault in an engine cylinder block.